Screening the Biosphere: The Fungicolous Fungus Trichoderma phellinicola, a Prolific Source of Hypophellins, New 17‐, 18‐, 19‐, and 20‐Residue Peptaibiotics1. Issue 5 (17th May 2013) - Röhrich, Christian René; Iversen, Anita; Jaklitsch, Walter Michael; Voglmayr, Hermann; Vilcinskas, Andreas; Nielsen, Kristian Fog; Thrane, Ulf; von Döhren, Hans; Brückner, Hans; Degenkolb, Thomas
Abstract To investigate the significance of antibiotics for the producing organism(s) in the natural habitat, we screened a specimen of the fungicolous fungus Trichoderma phellinicola (syn. Hypocrea phellinicola) growing on its natural host Phellinus ferruginosus. Results revealed that a particular group of non‐ribosomal antibiotic polypeptides, peptaibiotics, which contain the non‐proteinogenic marker amino acid, α‐aminoisobutyric acid, was biosynthesized in the natural habitat by the fungicolous producer and, consequently, released into the host. By means of liquid chromatography coupled to electrospray high‐resolution time‐of‐flight mass spectrometry, we detected ten 20‐residue peptaibols in the specimen. Sequences of peptaibiotics found in vivo were independently confirmed by analyzing the peptaibiome of an agar plate culture of T. phellinicola CBS 119283 (ex‐type) grown under laboratory conditions. Notably, this strain could be identified as a potent producer of 39 new 17‐, 18‐, and 19‐residue peptaibiotics, which display the same building scheme as the 20‐residue peptaibols found in the specimen. Two of the 19‐residue peptaibols are tentatively assigned to carry tyrosinol, a novel C‐terminal residue, as deduced from high‐resolution tandem mass‐spectrometry data. For the new peptaibiotics produced by T. phellinicola, the name 'hypophellin(s)', based on the teleomorph name, is introduced.